Naturally Occurring Chalcones with Aggregation-Induced Emission Enhancement Characteristics - Iwona Budziak-Wieczorek; Daniel Kamiński; Alicja Skrzypek; Anna Ciołek; Tomasz Skrzypek; Ewa Janik-Zabrotowicz; Marta Arczewska (Molecules, 2023)
In this paper, the natural chalcones: 2′-hydroxy-4,4′,6′-trimethoxychalcone (HCH), cardamonin (CA), xanthohumol (XN), isobavachalcone (IBC) and licochalcone A (LIC) are studied using spectroscopic techniques such as UV–vis, fluorescence spectroscopy, scanning electron microscopy (SEM) and single-crystal X-ray diffraction (XRD). For the first time, the spectroscopic and structural features of naturally occurring chalcones with varying numbers and positions of hydroxyl groups in rings A and B were investigated to prove the presence of the aggregation-induced emission enhancement (AIEE) effect. The fluorescence studies were carried out in the aggregate form in a solution and in a solid state. As to the results of spectroscopic analyses conducted in the solvent media, the selected mixtures (CH3OH:H2O and CH3OH:ethylene glycol), as well as the fluorescence quantum yield (ϕF) and SEM, confirmed that two of the tested chalcones (CA and HCH) exhibited effective AIEE behaviour. On the other hand, LIC showed a large fluorescence quantum yield and Stokes shift in the polar solvents and in the solid state. Moreover, all studied compounds were tested for their promising antioxidant activities via the utilisation of 1,1- diphenyl-2-picrylhydrazyl as a free-radical scavenging reagent as well as potential anti-neurodegenerative agents via their ability to act as acetylcholinesterase (AChE) and butyrylcholinesterase (BuChE) inhibitors. Finally, the results demonstrated that licochalcone A, with the most desirable emission properties, showed the most effective antioxidant (DPPH IC50 29%) and neuroprotective properties (AChE IC50 23.41 ± 0.02 μM, BuChE IC50 42.28 ± 0.06 μM). The substitution pattern and the biological assay findings establish some relation between photophysical properties and biological activity that might apply in designing AIEE molecules with the specified characteristics for biological application.